O anonimato na ordem jurídico-constitucional brasileira e suas implicações na internet - Bonotto, Ana Carolina Garcia (2017)
The present study analyzes the scope of protection of freedom of speech in order to verify the possibility of a rereading of the veto to anonymity in the Brazilian Constitution regarding the news Technologies of Information and Communication - ICT. To this end, it analyzes the possibility of anonymity based on the preservation of the right to privacy, and as a means of preserving freedom of speech. Freedom of speech and information is constituted by a consolidated legal system, the result of historical struggles and achievements, and currently emphasized by national and international regulations. In addition, they demonstrate the reach of the democratic conquest of many countries through the mobilization and voice of the people. Freedom of speech in Brazil is a fundamental right expressed by the Federal Constitution. This right, however, is limited to acts that do not hide the identity of the individual in his or her exercise. There are few Supreme Court Judgments dealing with this limitation clause, and those who refer it, are divided in opinions regarding the application of the institute. This context, add up with the new challenges of a postmodern society connected by networks and new media, exalts the need for new contours to this constitutional guarantee and to the institute of anonymity itself. While in the offline context the barriers off communication and information diffusion showed more robust, in the online context these barriers seem to have been largely broken and urgently require a thematic engagement with binding effect. In this sense, the reality of online anonymity arises clamoring to be scrutiny relating to the preservation of personal information. The society is still unaware of the handling, possibilities and risks of using the network, sometimes leading to procedural difficulties for the prosecution of infractions and crimes committed by the network. In specific, in the use of the Internet, the user can be identified through the crossing of data and identification of the IP (Internet Protocol), and difficultly can be anonymous, so it is spoken in relative anonymity. Based on International Directives and the Civil Internet Framework itself, can be observed the preservation of personal information by opening a new relationship between the institute of anonymity and the legal assets protected by the Brazilian Constitution.